A Comparative Study of Rhetorical Moves and Linguistic Features of Lecturers’ Theses and Dissertations Abstracts in Soft and Hard Science - Fadlila Ghifarina Gani; Eri Kurniawan (Passage, 2021)
Move analysis is a genre-based approach used to analyze academic writing and investigate the rhetorical pattern of the text such as academic paper, abstracts, thesis, etc. However, the analysis of rhetorical moves in the abstracts of lecturers’ final papers in different disciplines remains unexplored. The aim of this study is to identify and compare the rhetorical moves, steps, and linguistic features of the abstract of lecturers from four different disciplines. The researchers focused on the abstract of master theses and dissertations from each discipline. This study analyzed eight abstracts from English lecturers for the soft science field, Mathematic and Architectural lecturers for the hard science field in Universitas Pendidikan Indonesia. The Five Move Analysis by Hyland (2004) is used as the framework of this study. The findings showed that Move 1 - Introduction was the most common move in hard science abstracts, while in soft science, it was Move 4 - Product. Moreover, the most occur step in both fields was Step 2 of Move 1 – Making topic generalization and Step 1 of Move 5 – Deducing conclusion. For linguistics features, both of the fields mostly used active voice. While for the tense, hard science tended to use present tense, but soft science inclined to use past tense. The findings show that each field has different tendencies yet similarities in writing abstracts to highlight the essential things on each abstract.